Differential Angiogenic Gene Expression in TP53 Wild-Type and Mutant Ovarian Cancer Cell Lines - Davidson, Brittany Anne; Rubatt, Jennifer M.; Corcoran, David L.; Teoh, Deanna K.; Bernardini, Marcus Q.; Grace, Lisa A.; Soper, William John; Berchuck, Andrew; Siamakpour-Reihani, Sharareh; Chen, Wei; Owzar, Kouros; Murphy, Susan K.; et al. (Frontiers in Oncology, 2014)
Objectives: Underlying mechanisms regulating angiogenesis in ovarian cancer have not been completely elucidated. Evidence suggests that the TP53 tumor suppressor pathway and tumor microenvironment play integral roles. We utilized microarray technology to study the interaction between TP53 mutational status & hypoxia on angiogenic gene expression. Methods: Affymetrix U133A arrays were analyzed for angiogenic gene expression in 19 ovarian cancer cell lines stratified both by TP53 mutation status and A2780 wild-type (wt) TP53 vs. mutated (m) TP53 cell lines after treatment under hypoxic conditions or with ionizing radiation. Results: Twenty-eight differentially expressed angiogenic genes were identified in the mTP53 cell lines compared to wtTP53 lines. Five genes were upregulated in mTP53 cells: 40% involved in extracellular matrix (ECM) degradation (MMP10/15) and 60% in angiogenesis (FGFR3/VEGFA/EPHB4). Twenty-three genes were upregulated in wtTP53: nearly 22% were ECM constituents or involved in ECM degradation; over 40% were growth factors or mediators of angiogenesis. Five genes were upregulated in the A2780mTP53 cells: 40% involved in ECM remodeling (MMP10, ADAMTS1), 40% with pro-angiogenic activity (EFNB2, F2R), and 20% with anti-angiogenic properties (ADAMTS1). Three genes were upregulated in hypoxia treated cells compared to controls: 1 with anti-angiogenic activity (ANGPTL4) and 2 with pro-angiogenic activity (VEGFA, EFNA3). No significant gene fold changes were noted after exposure to radiation. Four genes continued to demonstrate significant differential expression (p≤0.05) after adjusting for multiple comparisons. These genes included ENG upregulation in wild-type lines and upregulation of FGF-20, ADAMTS1 & MMP10 in mTP53 lines. Conclusions: Our exploratory findings indicate that non-overlapping angiogenic pathways may be altered by TP53 mutations and hypoxic conditions in ththe tumor microenvironment. Further evaluation is needed for confirmation.